An evaluation of the use of smartboard technology in teaching at horizon international bilingual school in Hanoi, Vietnam (2013-2014) = Đánh giá việc sử dụng bảng thông minh trong đánh giá giảng dạy ở Trường song ngữ quốc tế Horizon Hà Nội. - Adams, Jacob Micheal (University of Languages and International Studies, 2017)
This research thesis is an evaluation of how SmartBoard technology was used at Horizon International Bilingual School (H.I.B.S.), in Hanoi, Vietnam during the 2013-2014 academic year. H.I.B.S.has classrooms equipped with the latest in technological learning devices, such as the SmartBoard. This thesis will show how this technology is viewed and used by students and teachers alike at H.I.B.S. I used anonymous surveys to collect qualitative data results, and respectively used qualitative analysis to show how this technology was used and viewed by individuals who taught for and attended H.I.B.S.during the 2013-2014 academic year. The main point of this thesis is to improve the use of modern technology in teaching, especially in the use of the SmartBoard, at H.I.B.S.in the following years to come.